Administrative regulation measures for foreign trade in the European union (on the example of the Republic of Poland) and in the Eurasian economic union (on the example of the Russian Federation) - V. A. Kardanov; V. N. Kulik (Вестник университета)
The European Union is the largest trading partner for the Eurasian Economic Union. The multi-integration of the Eurasian Economic Union with foreign countries practically guarantees a positive result. The issues, related with non-tariff measures regulating foreign trade, have been considered in the article. For the countries of the Eurasian Economic Union and the Russian Federation in particular, in the near future, the main task should be step-by-step standardization and elimination of almost all non-tariff barriers to trade, as these values significantly aggravate the counter-trade in goods and services and hinder further integration. And this concerns, above all, the development towards the European Union.